The Effect of 0.2% Hyaluronic Acid Cream on the Severity of Acute Radiodermatitis in Breast Cancer Patients: a Double-Blind Randomized Controlled Trial - Muchamad Apriyanto; Sigid Santosa, Novita Permatasari; Mira Oktarina, Dyah Ayu; Ekaputra, Ericko; Trisnowati, Niken; Budiyanto, Arief; Soebono, Hardyanto; Waskito, Fajar; Indrastuti, Niken (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Radiotherapy is an essential treatment in reducing the risk of breast cancer but can cause side effects such as acute radiodermatitis. This condition is the result of ionizing radiation damaging deoxyribonucleic acid (DNA) through reactive oxygen species (ROS) and inducing inflammatory responses, which lead to variable degrees of skin damage. Hyaluronic acid (HA) plays a role in triggering cell proliferation and keratinocyte differentiation while inhibiting lipid peroxidation caused by oxidative stress. Purpose: This study aims to determine the effectiveness of hyaluronic acid in reducing the degree of acute radiodermatitis using the Radiation Therapy Oncology Group (RTOG) score in breast cancer patients undergoing radiotherapy. Methods: This study was a double-blind randomized controlled trial. The samples were from patients diagnosed with breast cancer receiving radiotherapy. The treatment group received 0.2% HA cream, while the control group received a placebo The clinical appearance was evaluated weekly from the beginning of radiotherapy until two weeks post-radiotherapy using the RTOG score. Result: A total of 41 subjects were divided into two groups. RTOG score evaluation with intention-to-treat analysis and per-protocol analysis at weeks 3, 4, and 5 showed that the hyaluronic acid cream group experienced delayed onset of acute radiodermatitis compared to the placebo group. The log-rank test showed a significant difference in effectiveness between 0.2% HA cream compared to base cream in reducing the degree of acute radiodermatitis (p=0.035). Conclusion: The use of 0.2% HA cream was effective in reducing the severity of acute radiodermatitis in breast cancer patients undergoing radiotherapy.